Konsep Ilmu Ke MI an - Nurfadila, Himmatin; Nurjanah, Siti (MASALIQ, 2022)
Science is a system of meaning of reality and truth, sourced from revelation supported by reason and intuition. With the nadzar and fikr process, the ratio will be able to articulate, formulate propositions, express opinions, argue, make analogies, make decisions, and draw conclusions. In the Islamic worldview, science is closely related to faith, 'aql, qalb, and taqwah. Not only is knowledge systematically collected, but science is also a methodology. Where the right methodology will certainly not conflict with the right one. Peter R Senn in Science in Perspective describes more firmly that “Science is like a building made of bricks. These stones or basic elements are never directly found in the natural environment. Science and its derivations appear repeatedly in the Qur'an and occupy the second position after the word monotheism. In Sahih Bukhari, the chapter of knowledge (kitab al-'ilm) is juxtaposed with the chapter of faith (Kitab al-iman). This shows how the most important and comprehensive concept contained in the Qur'an and as-Sunnah is the science ('ilm) of Madrasah Ibtidaiyah at the elementary school level which is taken for 6 years organized by the Ministry of Religion. Scientific planting at this level becomes the basic concept in further education.